(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Vitamin D deficiency has been increasingly recognized as a potential factor influencing endocrine regulation beyond calcium metabolism. However, its relationship with peripheral thyroid hormone activation remains insufficiently clarified, particularly in populations with high rates of thyroid dysfunction. Objective: This study aimed to evaluate the association between serum 25-hydroxyvitamin D [25(OH)D], intact parathyroid hormone (PTH), thyroid-stimulating hormone (TSH), and the FT3/FT4 ratio as an indicator of peripheral thyroid hormone conversion. Methods: A retrospective cross-sectional study was conducted at the in-vitro division of Institute of Nuclear Medicine and Allied Sciences (INMAS), Mohakhali, Dhaka. A total of 138 participants were included. Serum levels of TSH, Free triiodothyronine (FT3), Free thyroxine (FT4), 25(OH)D, PTH, and calcium were measured using chemiluminescence immunoassay (CLIA). Due to non-normal distribution, TSH values were log-transformed prior to analysis. Correlations were assessed using Pearson’s coefficient, and linear regression was performed to determine explanatory power. Results: The study population demonstrated marked thyroid dysfunction and widespread vitamin D deficiency. Serum 25(OH)D levels showed a strong positive correlation with the FT3/FT4 ratio (r = +0.69, p < 0.001). Log-transformed TSH exhibited a significant inverse correlation with the FT3/FT4 ratio (r = −0.64, p < 0.001), explaining 40.5% of its variability. Intact PTH showed a weaker but statistically significant inverse association with the FT3/FT4 ratio (r = −0.23, p = 0.027), accounting for 5.5% of the variation. Conclusion: Higher vitamin D levels are linked to enhanced peripheral thyroid hormone conversion, while greater stimulation of the thyroid axis correlates with a decreased FT3/FT4 ratio. Vitamin D status shows a stronger relationship with thyroid hormone activation compared to PTH. These results suggest the importance of vitamin D in thyroid hormone metabolism and its potential role in endocrine evaluation, indicating the need for further prospective studies to explore the mechanisms involved. Bangladesh J. Nuclear Med. 28(2): 275-281, July 2025